SUPER BIO-VOXEL ENTITY - SHADID, RAMZI (My University, 2020)
Super Entity that can adapt and change according to its inhabitants needs, not only for today’s society, but also for generations to come. One which elicits biological and evolutionary process in essence. A transformative architecture that can sustain an active dialogue with its inhabitants, whose trend are in constant flux, results in a reunification between humanity and its time-sensitive, responsive natural habitat. The aim of this Project is to redefine a new housing entity derived from the Palestinian needs, context and vision. Housing has been a major challenge for the rising population during last decades, especially in developing countries. A frequent question still asks itself, what makes people satisfy and comfortable? And what factors make their living space and city livable? The approach is to focus on social fabric, spatial configuration, environmental context and economic development. "Architecture as part of life, experience and storytelling" is a concept that should be followed. Buildings should adapt to our space, our functionalities and our needs that change permanently - and even to our sense of beauty itself in continuous motion, growth and dynamism.